PHYTOCHEMICAL SCREENING OF ANCHOTE (COCCINIA ABYSSINICA (LAM.)) AND EFFECT OF EXTRACT VIA AEROBIC EXERCISE ON ENDURANCE PERFORMANCE - Olkaba, Getahun Hambisa; Ayalew, Abnet (Stadium - Hungarian Journal of Sport Sciences, 2024)
Many aspects affect sports performance, and nutrition may be one of the most important. The study aimed to examine the phytochemical composition and assess the impact of supplementing Anchote (Coccinia abyssinica (Lam.)) with aerobic exercise on the endurance performance of the Mattu Kenema male football club. Eighteen players from the Mattu Kenema football team were chosen based on an experimental research methodology. The selected athletes were divided into three groups at random: the supplement group (SG = 6), the aerobic exercise group (AG = 6), and the supplement with the aerobic exercise group (SAG = 6). Every day, members of the SG group took an Anchote (Coccinia abyssinica (Lam.)) supplement, while AE spent 45–60 minutes exercising aerobically. SAG took both interventions for 12 weeks. Pre-tests and post-tests were conducted on all parameters, such as the 12-minute run test and push-up. The phytochemical screening result of Anchote (Coccinia abyssinica (Lam.)) extract showed the presence of various secondary metabolites such as phenol, flavonoid, tannin, glycoside, steroid, and terpenoids. The proximate composition of this extract indicates the higher content of carbohydrates (69%) and the lower fat value (2.1%). Based on the study, 12 weeks of Achote (Coccinia abyssinica (Lam.)) consumption combined with aerobic exercise was thus shown to improve players' fitness levels at Mattu Kenema male football club. Based on the findings, Anchote (Coccinia abyssinica (Lam.)) supplement associated with aerobic exercise would enhance endurance performance due to the extract's secondary metabolites such as flavonoid, tannin, and phenol.